A New Model of Website-Based Humanistic Academic Supervision to Improve The Teaching Quality of High School Teachers: '- - Satyawati, Sophia Tri; Dwikurnaningsih, Yari; Nabila, Nabila; Andianti, Yohana Putri (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop, validate, and examine the acceptability of an academic supervision model that integrates a humanistic approach with a web-based platform to support high school teachers’ well-being. Employing a mixed-methods design within a Research and Development (R&D) framework, the study included needs analysis, product design, expert validation, and field trials involving 20 teachers and one principal. Data were collected through in-depth interviews, document analysis, and questionnaires, and were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing or verification. The findings indicate a strong need for more dialogical, flexible, and collaborative supervision. The developed model received high validation scores from academic supervision experts (93.06%) and information technology experts (84.73%). The user acceptance test demonstrated an excellent result (94.92%), confirming that this model successfully fostered a more comfortable, meaningful supervision experience that also motivated teachers. This study contributes a practical, evidence-based supervision model that is replicable and demonstrates how technology can effectively support humanistic relationships to enhance teaching quality and teacher well-being in the digital era.